2006
DOI: 10.1086/505059
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐Supported Involvement of Entire Faculties in Examination of Student Data for Instructional Improvement

Abstract: Student data are gaining increased attention in education, spurred by accountability policies such as those contained in the federal No Child Left Behind legislation. Student data are useful for informing classroom practice, and userfriendly technologies for organizing and accessing data are enabling access by all teachers. In this study, we examine the efforts of three schools to involve entire faculties in the examination of student data, supported by efficient data systems. Results indicate the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(183 citation statements)
references
References 16 publications
6
173
0
4
Order By: Relevance
“…Research has identified the critical role of school leadership in providing the necessary conditions for using achievement data strategically (Copland, 2002;Supovitz & Klein, 2003;Wayman & Stringfield, 2006a;Young, 2006).Specifically, there is a need for school leaders to articulate and support formal processes for accountability, ownership and responsibility for the effective use of achievement data (Masters, 2010;O'Neill et al, 2010). O'Neill et al, (2010, p. 19) asserted that "the importance of counselling, knowledge and use of data, relationships with students, relationships with parents, strategic planning and the importance of the development of an appropriate culture" are the recurring themes elicited in interviews with leaders of top performing schools.…”
Section: The Role Of School Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has identified the critical role of school leadership in providing the necessary conditions for using achievement data strategically (Copland, 2002;Supovitz & Klein, 2003;Wayman & Stringfield, 2006a;Young, 2006).Specifically, there is a need for school leaders to articulate and support formal processes for accountability, ownership and responsibility for the effective use of achievement data (Masters, 2010;O'Neill et al, 2010). O'Neill et al, (2010, p. 19) asserted that "the importance of counselling, knowledge and use of data, relationships with students, relationships with parents, strategic planning and the importance of the development of an appropriate culture" are the recurring themes elicited in interviews with leaders of top performing schools.…”
Section: The Role Of School Leadershipmentioning
confidence: 99%
“…Further research into leadership practices regarding the use of student achievement data revealed the need for school and system leadership to promote a culture of continuous improvement (Wayman & Stringfield, 2006a;Young, 2006). To illustrate, Young et al (2010) stated that "The Principal's leadership is crucial to setting expectations for school staff to consider data as decision inputs and to creating supportive environments in which teachers can share the successes and failures associated with assessment results" (p. 19).…”
Section: The Role Of School Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Ook deze doelen kunnen voortvloeien vanuit een verantwoordingsperspectief, zoals het gebruik van informatie om leerkrachten ter verantwoording te stellen voor de onderwijskwaliteit op school of om de schoolkwaliteit te verantwoorden ten opzichte van de onderwijsinspectie (Coburn & Talbert, 2006;Schildkamp & Kuyper, 2010;Wayman & Stringfield, 2006), of vanuit een schoolontwikkelingsperspectief, zoals het gebruik van informatie om de schoolkwaliteit te monitoren, verbeteracties voorop te stellen of voor beleidsontwikkeling en -planning (Coburn & Talbert, 2006;Schildkamp & Kuyper, 2010;Schildkamp, Rekers-Mombarg, & Harms, 2012).…”
Section: Doelen Met Betrekking Tot Informatiegebruikunclassified
“…les incidences de ces recherches à grand déploiement teintent immanquablement les débats en matière de politiques éducatives (Gustafsson, 2008). les responsables en administration scolaire et des instances gouvernementales ainsi que les parents utilisent ces résultats dans le but de concevoir des plans d'aide à la réussite, d'allouer des ressources, d'orienter les prises de décisions et de mettre en place des politiques éduca-tives (Barker, 2004 ;Brown, 1999 ;coburn & talbert, 2006 ;copland, 2003 ;Kerr, Marsh, ikemoto, darilek, & Barney, 2006 ;Kornhaber, 2004 ;wayman & stringfield, 2006a, 2006byoung, 2006). en dépit du sérieux accordé aux résultats de ces enquêtes à grande échelle, ces dernières ouvrent aujourd'hui la voie à des considérations plus larges concernant l'administration de ce type de test.…”
unclassified